A new species of Parotocinclus (Siluriformes: Loricariidae) from the upper Rio São Francisco, Brazil - A., Pablo Lehmann; Reis, Roberto E. (Zootaxa, 2012)
A new species of the hypoptopomatine loricariid Parotocinclus is described based on material from three rivers belongingto the upper and middle Rio São Francico basin, the Rio das Velhas and Rio Jequitaí on the right margin and the RioParacatu on the left margin. The new species is readily distinguished from all congeners by having the abdomencompletely devoid of dermal plates between the pectoral girdle and the anus, by differences in rostral and postrostral plates, and by having the pectoral girdle covered by skin medially and exposed and supporting odontodes only laterally.